2015
DOI: 10.1007/s10661-015-4980-x
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical behaviour of PM10 aerosol constituents under the influence of succeeding anticyclonic/cyclonic situations: case of Sfax City, southern Tunisia

Abstract: The present study investigates the geochemical behaviour of PM10 aerosol constituents (Cl, Na, Si, Al, Ca, Fe, Mg, Mn, Pb, Zn, S) at Sfax City (Tunisia) under succeeding meteorological conditions, including short-lived anticyclonic, cyclonic and prolonged anticyclonic situations. The results revealed daily total concentrations fluctuating between 4.07 and 88.51 μg/m(3). The highest level recorded was noted to occur under the effect of the short-lived anticyclonic situation characterized by low wind speeds. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…At site S23, their importance is possibly related to the phenomenon of road dust resuspension. This result has already been proved by Bahloul et al (2015b). The temporal evolution of the particulate deposits constituents at the two sites S14 and S23 also shows a great fluctuation (Tables 3 and 4).…”
Section: Temporal Evolution Of Particulate Deposits Constituentssupporting
confidence: 72%
See 3 more Smart Citations
“…At site S23, their importance is possibly related to the phenomenon of road dust resuspension. This result has already been proved by Bahloul et al (2015b). The temporal evolution of the particulate deposits constituents at the two sites S14 and S23 also shows a great fluctuation (Tables 3 and 4).…”
Section: Temporal Evolution Of Particulate Deposits Constituentssupporting
confidence: 72%
“…The marked frequency of relatively high wind speeds exceeding 7 m/s (25% of the total observations) in the Monastir region could reinforce this phenomenon. Bahloul et al (2015b) showed that velocities greater than 7 m/s significantly accentuate Regressions between mean sea level pressure and biweekly flow deposits trough the two studied sites (S14 and S23) the phenomenon of dust resuspension. The relatively high velocities normally promote the dilution of air components (including suspended particulate matter).…”
Section: Temporal Evolution Of Particulate Deposits Constituentsmentioning
confidence: 83%
See 2 more Smart Citations
“…This area is marked by the presence of the SIAPE industry (Industrial Society of Phosphoric Acid and Fertilizers), which has released large amounts of phosphogypsum wastes for 40 years. These phosphogypsum wastes are a significant source of phosphates, chloride and sulphates for seawater and may explain the high chemical oxygen demand in the surface waters of Sfax (Bahloul et al, 2015;Drira et al, 2016). Besides the SIAPE industry and its phosphogypsum wastes, the Sfax coasts comprises several industrial areas related to textiles, tanneries, salt, olive oil, food processing, construction materials, ceramics and glass.…”
Section: Study Areamentioning
confidence: 99%